Sustainable city logistics concepts: Elements and conceptualization - Kovač Milovan G.; Tadić Snežana R.; Krstić Mladen D. (Tehnika, 2023)
Defining and the application of sustainable city logistics concepts is a prerequisite for achieving sustainability in urban areas. The scientific literature is abundant with research that highlights individual technologies, initiatives, measures and approaches as indispensable elements of sustainable concepts. Although a relatively large set of city logistics concepts is analyzed in the literature, there is no generally accepted set of guidelines for defining sustainable city logistics concepts. This article tries to fill that literature gap. The main contribution of this article is, on basis of the review of relevant literature in the field, to demonstrate how potentially sustainable city logistics concepts could be conceptualized by combining different building elements (technologies, initiatives, measures, and approaches).